DESIGN AND MANUFACTURE A BANANA FIBER EXTRACTION MACHINE FOR SMALL AND MEDIUM-SCALE HANDICRAFT PRODUCTION - Cong Chi, Tran; Thi Phuong Hoa, Ta; Huy Dai, Vu; Van Tinh, Pham (Journal of Forestry Science and Technology, 2023)
Currently, by-products from banana trees such as banana sheath and leaves are discarded, which is very wasteful and causes environmental pollution. However, in the world, these materials are considered a significant resource that can be used to produce natural fibers and create handicraft products that are aesthetically valuable, economically viable, and environmentally friendly. This article introduces the research results on designing and manufacturing a banana fiber extraction machine for the production of handicrafts on a small to medium scale in Vietnam. The machine was designed through calculations, model building, and software testing before being manufactured and assembled. After assembly and completion, the banana fiber extraction machine was tested under no load and under load to evaluate its fiber processing capability. Three different processing modes corresponding to different motor speeds of 750 rpm, 900 rpm, and 1,050 rpm were tested to evaluate the banana fiber extraction rate. The results showed that the machine functioned reliably across all three modes, with extraction rates of 10.1%, 11.2%, and 10.8% achieved at motor speeds of 750, 900, and 1050 rpm, respectively. Therefore, this banana fiber extraction machine can be used to extract banana fibers and meet the requirements of producing handicraft materials in Vietnam.